Thin film phase transformation kinetics: From theory to experiment. (November 2016) - Moghadam, M.M.; Voorhees, P.W.
Abstract: The Level-set method simulation is used to address the effect of finite size on kinetics of thin film phase transformations. The results are first interpreted using the classic Johnson-Mehl-Avrami-Kolmogorov (JMAK) description of a nucleation and growth phase transformation that yields the average Avrami exponent and rate constant as a function of film thickness. The analysis reveals that the JMAK framework can yield a spurious thickness dependent activation energy for the transformation. To overcome this problem, we propose an analysis that allows all the kinetic parameters, including the nucleation rate and interface growth velocity in films to be determined from experiment. Graphical abstract: